The beneficial effects of Ganoderma lucidum on cardiovascular and metabolic disease risk - Sze Wa Chan; Brian Tomlinson; Paul Chan; Christopher Wai Kei Lam (Taylor & Francis Group, 2021)
Context Various herbal medicines are thought to be useful in the management of cardiometabolic disease and its risk factors. Ganoderma lucidum (Curtis) P. Karst. (Ganodermataceae), also known as Lingzhi, has received considerable attention for various indications, including some related to the prevention and treatment of cardiovascular and metabolic disease by ameliorating major cardiovascular risk factors. Objective This review focuses on the major studies of the whole plant, plant extract, and specific active compounds isolated from G. lucidum in relation to the main risk factors for cardiometabolic disease. Methods References from major databases including PubMed, Web of Science, and Google Scholar were compiled. The search terms used were Ganoderma lucidum, Lingzhi, Reishi, cardiovascular, hypoglycaemic, diabetes, dyslipidaemia, antihypertensive, and anti-inflammatory. Results A number of in vitro studies and in vivo animal models have found that G. lucidum possesses antioxidative, antihypertensive, hypoglycaemic, lipid-lowering, and anti-inflammatory properties, but the health benefits in clinical trials are inconsistent. Among these potential health benefits, the most compelling evidence thus far is its hypoglycaemic effects in patients with type 2 diabetes or hyperglycaemia. Conclusions The inconsistent evidence about the potential health benefits of G. lucidum is possibly because of the use of different Ganoderma formulations and different study populations. Further large controlled clinical studies are therefore needed to clarify the potential benefits of G. lucidum preparations standardised by known active components in the prevention and treatment of cardiometabolic disease.